MEMAHAMI HAMBATAN DOSEN DAN MAHASISWA DALAM PERKULIAHAN ONLINE : FENOMENA ANTISIPASI PENYEBARAN VIRUS COVID-19 - Adiyanto, Wiwid (Master of Communication Science Program, Universitas Diponegoro, 2020)
The problem that has occurred in lectures since the COVID-19 virus outbreak was the transformation of the class technical system from face-to-face into online class. Communication technology plays a very important role in the communication of lecturers and students in online class. Online class are inseparable from problems in the use of technology and changes in the habits of face-to-face lectures. This study aims to describe the obstacles of lecturers and students in online lectures related to the anticipation of the spread of the COVID-19 virus. This study uses Media Ecology theory as a foundation for thinking. This research is a phenomenological study with a qualitative descriptive approach. Primary data were obtained from the results of indepth interviews with 6 informants who were lecturers and students in Yogyakarta. The results of this study indicate a obstacle model of online class. There are two types of obstacles that are interconnected in the online class process, namely the obstacles during the class and the obstacles outside the class. This study discusses the differences in the meaning of online class between lecturer and student informants. The findings also show 6 similarities in the patterns of barriers from informants. This research shows that communication technology is not value-free.